Thaddeus Stevens : Civil War revolutionary, fighter for racial justice - Levine, Bruce C., 1949- (Simon & Schuster, 2021)
A portrait of the nineteenth-century statesman includes discussions of Stevens's decades-long fight against slavery, key role in the Union war effort, and postwar legislation for American racial justice.